Haunted hayride - Klein, Abby; McKinley, John, 1956- (New York, NY : Scholastic Inc., 2016)
"Freddy's friends can't wait to try the haunted hayride at the Halloween festival -- especially Freddy's new friend, Josh. The hayride is supposed to be really scary! But when Max bets Josh that Freddy will be too much of a fraidy-cat to join them, Freddy is determined to be brave ... no matter what!"--Page [4] of cover.
Appeals to 2nd-3rd graders.
Reading level grade 2.
620L
Decoding demand: 64 (high) Semantic demand: 88 (very high) Syntactic demand: 75 (high) Structure demand: 82 (very high)
Accelerated Reader AR
Keywords: Halloween -- Juvenile fiction; Hayrides -- Juvenile fiction; Courage -- Juvenile fiction